Emergent Innovative Mathematics Pedagogies in Contemporary Education: Foundations Towards the Development of a Pedagogical Framework - Jovito B. Crodua Jr.; Jay Fie P. Luzano (Future Science / FSH-PH Publications, 2026)
There is a growing need for more innovative approaches to teaching mathematics in classrooms worldwide. Teachers are expected to deliver pedagogies that cater to diverse learners, engage them in meaningful mathematical learning, and provide access to opportunities for all students to succeed in mathematics. This study sought to explore the lived experiences of teachers in implementing innovative mathematics pedagogies (IMP) and examine the foundations for the development of pedagogical framework that could guide other educators in teaching mathematics. This transcendental phenomenological study investigated senior high school mathematics teachers from public secondary schools in Region XI (Davao Region), Philippines, identified for their instructional innovations. Participants in the study were 10 purposively selected senior high school mathematics teachers. In-depth interviews were used as the research methodology to collect in-depth narratives of teachers’ lived experiences with IMP. Findings from the study provided insight into IMP from the teachers’ perspectives. Three main themes, Mathematical Engagement, Mathematical Representation, and Mathematical Action and Expression were found to characterize innovative teaching of mathematics. These themes included 14 subthemes, including game-based, contextualized, peer-based, project-based and experiential learning for mathematical engagement. Mathematical representation includes differentiated, technology-enhanced, use of SIMs, and asynchronous learning. Consequently, inquiry-based, assessment-based, problem-based, reflection-based, and remediation and enrichment math learning compose mathematical action and expression. These themes and subthemes collectively provide insight into teachers’ instructional practices used to engage students in mathematical learning.